Biomimetic Materials: Stretch‐Healable Molecular Nanofibers (Adv. Theory Simul. 10/2020). Issue 10 (5th October 2020) - Han, Yanxiao; Langer, Michal; Medved', Miroslav; Otyepka, Michal; Král, Petr
Abstract : Ultra‐stretchable self‐healable nanofibers have been designed by Michal Otyepka, Petr Král, and co‐workers, inspired by spider silk, which has fascinating properties and molecular structures. The nanofibers, reported in article number 2000094, are formed by assemblies of coronene and perfluorocoronene molecular flakes covalently connected by short flexible molecular linkers. Molecular dynamics simulations revealed that the speed of forced stretching and released reassembly of the nanofibers depend on the environment humidity.